Client satisfaction and quality of health care in rural Bangladesh - Aldana Jorge Mendoza; Piechulek Helga; Al-Sabir Ahmed (The World Health Organization, 2001)
OBJECTIVE: To assess user expectations and degree of client satisfaction and quality of health care provided in rural Bangladesh. METHODS: A total of 1913 persons chosen by systematic random sampling were successfully interviewed immediately after having received care in government health facilities. FINDINGS: The most powerful predictor for client satisfaction with the government services was provider behaviour, especially respect and politeness. For patients this aspect was much more important than the technical competence of the provider. Furthermore, a reduction in waiting time (on average to 30 min) was more important to clients than a prolongation of the quite short (from a medical standpoint) consultation time (on average 2 min, 22 sec), with 75% of clients being satisfied. Waiting time, which was about double at outreach services than that at fixed services, was the only element with which users of outreach services were dissatisfied. CONCLUSIONS: This study underscores that client satisfaction is determined by the cultural background of the people. It shows the dilemma that, though optimally care should be capable of meeting both medical and psychosocial needs, in reality care that meets all medical needs may fail to meet the client?s emotional or social needs. Conversely, care that meets psychosocial needs may leave the clients medically at risk. It seems important that developing countries promoting client-oriented health services should carry out more in-depth research on the determinants of client satisfaction in the respective culture.